Profil Peresepan Antipsikosis di Unit Rawat Jalan Rumah Sakit Mitra Keluarga Bekasi Timur Periode April – Mei 2021 - Eka Rusmana, Wempi; Yuliyanti, Yuliyanti (Cerdika: Jurnal Ilmiah Indonesia, 2022)
One of the global burdens currently engulfing the world is the COVID-19 pandemic. But before COVID-19 was declared a pandemic by the WHO, the world was struggling with the global burden of mental disorders. WHO states that depression and anxiety are mental disorders with the highest frequency. Mental disorders are one of the health problems that often go unnoticed. To treat mental disorders, antipsychotic therapy is needed which can be obtained at various health facilities, one of which is the Mitra Keluarga Hospital, East Bekasi, which serves patients with mental disorders. Antipsychotics are useful in the therapy of acute and chronic psychosis, a mental disorder such as dreams and imaginary thoughts (hallucinations) and normalize abnormal behavior. The purpose of this study was to determine the profile of antipsychotic prescribing in the pharmacy outpatient unit at Mitra Keluarga Hospital, East Bekasi for the period April – May 2021. This study was conducted using a quantitative descriptive method by taking primary data from doctor's prescriptions containing antipsychotics. The results obtained can see the profile of the most widely used antipsychotic prescribing based on the active substance, drug class, drugs used concurrently with antipsychotic drugs and the most widely used antipsychotic drugs by gender. The final analysis results obtained can assist in the procurement of antipsychotic drugs in health facilities.